Hybrid Metal Catalysts as Valuable Tools in Organic Synthesis: An Overview of the Recent Advances in Asymmetric C─C Bond Formation Reactions - Isabella Rimoldi; Giulia Coffetti; Raffaella Gandolfi; Giorgio Facchetti (Molecules)
Carbon–carbon bond formation represents a key reaction in organic synthesis, resulting in paramount importance for constructing the carbon backbone of organic molecules. However, traditional metal-based catalysis, despite its advantages, often struggles with issues related to efficiency, selectivity, and sustainability. On the other hand, while biocatalysis offers superior selectivity due to an extraordinary recognition process of the substrate, the scope of its applicable reactions remains somewhat limited. In this context, Artificial Metalloenzymes (ArMs) and Metallo Peptides (MPs) offer a promising and not fully explored solution, merging the two fields of transition metal catalysis and biotransformations, by inserting a catalytically active metal cofactor into a customizable protein scaffold or coordinating the metal ion directly to a short and tunable amino acid (Aa) sequence, respectively. As a result, these hybrid catalysts have gained attention as valuable tools for challenging catalytic transformations, providing systems with new-to-nature properties in organic synthesis. This review offers an overview of recent advances in the development of ArMs and MPs, focusing on their application in the asymmetric carbon–carbon bond-forming reactions, such as carbene insertion, Michael additions, Friedel–Crafts and cross-coupling reactions, and cyclopropanation, underscoring the versatility of these systems in synthesizing biologically relevant compounds.